2019
DOI: 10.1515/mammalia-2018-0117
|View full text |Cite
|
Sign up to set email alerts
|

Composition and diversity of bat assemblages at Arabuko-Sokoke Forest and the adjacent farmlands, Kenya

Abstract: Recognized as a global biodiversity hotspot, coastal forests in eastern Africa are currently reduced to fragments amidst human modified habitats. Managing for biodiversity depends on our understanding of how many and which species can persist in these modified areas. Aiming at clarifying how habitat structure changes affect bat assemblage composition and richness, we used ground-level mist nets at Arabuko-Sokoke Forest (ASF) and adjacent farmlands. Habitat structure was assessed using the point-centered quarte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…The current study investigated diversity and abundance of invertebrate in the interior of ASF and surrounding farmland. The ASF is a legally protected area, characterised by indigenous vegetation typical of the east African coastal forests [10,17] , while the farmland habitat is completely disturbed and modified into an agricultural landscape. Because the two contrasting habitats had been shown to host various types of insectivorous bat species [9,10] , there was need to provide data on diversity and abundance of invertebrates, which are the primary food items eaten by these bats.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The current study investigated diversity and abundance of invertebrate in the interior of ASF and surrounding farmland. The ASF is a legally protected area, characterised by indigenous vegetation typical of the east African coastal forests [10,17] , while the farmland habitat is completely disturbed and modified into an agricultural landscape. Because the two contrasting habitats had been shown to host various types of insectivorous bat species [9,10] , there was need to provide data on diversity and abundance of invertebrates, which are the primary food items eaten by these bats.…”
Section: Discussionmentioning
confidence: 99%
“…The ASF is a legally protected area, characterised by indigenous vegetation typical of the east African coastal forests [10,17] , while the farmland habitat is completely disturbed and modified into an agricultural landscape. Because the two contrasting habitats had been shown to host various types of insectivorous bat species [9,10] , there was need to provide data on diversity and abundance of invertebrates, which are the primary food items eaten by these bats. The results of our study indicated that the farmland in the eastern part of ASF as well as the interior of ASF and had similar invertebrate abundance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations